Export-led growth hypothesis in Malaysia : an investigation using bounds test - Choong, Chee Keong; Yusop, Zulkornain; Liew, Venus Khim Sen (Sunway University College, 2005)
The objective of this paper is to test the validity of the export-led growth hypothesis in the Malaysian economy using a more comprehensive sample period and a recent technique, that is, the bounds testing approach. Based on this model, both exports and labour force have stimulated positive adjustment to economic growth, whereas variables such as imports, exchange rate and the East Asian financial crisis are found to influence growth negatively. Moreover, a cointegrated relationship between exports and economic growth was detected in both the long and short runs. Further analysis showed that exports Granger-cause economic growth in the period of study. Thus, this study provides further evidence to support the export-led growth hypothesis in the Malaysian economy.